Stakeholders’ experience in community for smoking cessation and promotion of smoke-free home - Suteerangkul, Peeraya; Rawiworrakul, Tassanee; Kalampakorn, Surintorn; Saradhuldhat, Galaya; Addjanagitti, Patcharin; Panupus, Thapanee (Thai Journal of Nursing, 2022)
The purpose of this qualitative research was to study the experiences of stakeholders in community for smoking cessation and promotion of smoke-free home. The participants were smokers, families of smokers at home, community leaders, and registered nurses. A total of 24 informants was purposively selected from those with experience in tobacco control. Data were collected using a focus group guideline. Data were analyzed by content analysis. The results showed that quitting smoking and promoting smoke-free homes were as follows. 1) Motivating and adjusting attitudes, 2) assessing the 5As, intention to quit, and the stage of change, 3) creating a smoke-free environment for the health of the people. However, the home must be strictly smoke-free and professional nurses take care of family health, and 4) the community has sustained continuous participation with community policies building a network of cooperation with internal and external communities including strengthening the community and continuing to be sustainable.